2022
DOI: 10.1055/a-1862-3112
|View full text |Cite
|
Sign up to set email alerts
|

Empfehlungen zum Umgang mit der elektronischen Zigarette (E-Zigarette)

Abstract: Raucher:innen soll die E-Zigarette nicht zur Tabakentwöhnung empfohlen werden. Im Gegensatz zu Nikotinersatztherapie (NET) oder Medikamenten zur Unterstützung der Tabakentwöhnung werden E-Zigaretten von der Mehrheit der ausstiegswilligen Raucher:innen dauerhaft genutzt. Das anhaltende Inhalieren des E-Zigaretten-Aerosols beinhaltet Gesundheitsrisiken, deren Ausmaß bisher nicht abschätzbar ist. Raucher:innen, die auf E-Zigaretten umsteigen, haben ein erhöhtes Rückfallrisiko.Sollen lungenkranke Raucher:innen die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…A secondary analysis of a Cochrane systematic review of trials of e-cigarettes for cigarette cessation also demonstrated that the biomarkers are lower when switching to e-cigarettes or dual use compared to combustible cigarette smoking ( 4 ). Nevertheless, critics of harm reduction repeatedly portray dual use as dangerous, and sometimes even more so than continued exclusive cigarette smoking ( 5 , 6 ). By using the term “dual use,” guidelines suggest that there is a generally recognized definition of dual use that forms the basis of these studies and thus for guideline recommendations.…”
Section: Add-on Vs Displacement Dual Usementioning
confidence: 99%
See 1 more Smart Citation
“…A secondary analysis of a Cochrane systematic review of trials of e-cigarettes for cigarette cessation also demonstrated that the biomarkers are lower when switching to e-cigarettes or dual use compared to combustible cigarette smoking ( 4 ). Nevertheless, critics of harm reduction repeatedly portray dual use as dangerous, and sometimes even more so than continued exclusive cigarette smoking ( 5 , 6 ). By using the term “dual use,” guidelines suggest that there is a generally recognized definition of dual use that forms the basis of these studies and thus for guideline recommendations.…”
Section: Add-on Vs Displacement Dual Usementioning
confidence: 99%
“…The WHO, known to be rather critical of e-cigarettes, stated in its report on electronic nicotine and non-nicotine delivery systems (EN&NNDS): “There is conclusive evidence that: completely substituting EN&NNDS for combustible tobacco cigarettes reduces users' exposure to numerous toxicants and carcinogens present in combustible tobacco cigarettes; …” ( 17 ). The International Agency for Research on Cancer, which forms part of the WHO, states on their website ( 18 ): “E-cigarettes have the potential to reduce the enormous burden of disease and death caused by tobacco smoking if most smokers switch to e-cigarettes and public health concerns are properly addressed.” Despite this encouraging assessment, many consider the simultaneous consumption of combustion cigarettes and ENDS as harmful, and the risk of so-called dual use is cited as a strong argument against recommending ENDS use ( 5 , 6 ). As stated above, the term dual use is not generally well-defined and negative effects of dual use beyond those of exclusive cigarette smoking have not been scientifically substantiated.…”
Section: Add-on Vs Displacement Dual Usementioning
confidence: 99%